TINJAUAN SISTEM OPERASI FUNGSI DAN IMPLEMENTASINYA DALAM KOMPUTER PRIBADI - Hijrah Hijriah; Milka Afifah Rahmatillah; Zaehol Fatah (Jurnal Padamu Negeri, 2025)
An operating system is a core component of a personal computer that acts as a bridge between hardware and software, and allows users to interact with the system efficiently. This article presents a comprehensive overview of the basic functions of an operating system, such as process management, memory management, device management, and file systems, and how these functions are implemented in various types of personal computers. The discussion includes the evolution of operating systems over time, the underlying basic architecture, and a comparison of implementations between popular operating systems such as Windows, MacOS, and Linux. Through a descriptive-qualitative approach, this study aims to provide a deeper understanding of the important role of operating systems in supporting the performance and stability of personal computers. The results of the observation show that despite differences in technical approaches between platforms, the basic principles of operating systems remain consistent in providing a safe, stable, and structured working environment for users and applications.